Common causes of hearing impairment among children less than 8 years of age in District Bahawalpur, Punjab Pakistan - Safdar Ali; Muhammad Sikander Ghayas Khan; Laiba Zahid (Journal of the Pakistan Medical Association, 2022)
Objective: To find out the common causes of hearing loss among young children, and to compare the causes along gender lines. Method: The cross-sectional study was conducted from September 2020 to March 2021 at two government hospitals and one private clinic in Bahawalpur, Pakistan, and comprised children of either gender aged <8 years with complaint of decreased hearing. They were examined and tested for hearing impairment. Data was analysed using SPSS 22. Results: Of the 328 subjects, 164(50%) each were girls and boys. The overall mean age was 4.20±2.08 years. Sensorineural hearing loss was found in 178(54.3%), cases, conductive in 118(36%) and mixed type in 32(9.8%). Otitis media with effusion 89(27.1%) was the commonest cause of hearing impairment, followed by consanguinity 73(22.3%). There was no significant difference between the male and female children (p>0.05). Conclusion: Otitis media with effusion was the commonest cause of hearing impairment, followed by consanguinity. Gender had no significant role to play in this regard. Key Words: Hearing impairment, Children, Otitis media with effusion, Consanguinity, Bahawalpur.